2004
DOI: 10.1186/1471-2210-4-21
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the potential role of sulfite radical in morphine-associated histamine release

Abstract: BackgroundIntravenous morphine use is associated with elevated histamine release leading to bronchoconstriction, edema and hemodynamic instability in some patients. This study evaluated the possibility that sulfite, which is present as a preservative in many morphine preparations, might contribute to histamine release in vitro.ResultsThe human mast cell line, HMC-1, was exposed to various morphine concentrations, in the absence of sulfite, under cell culture conditions. Clinically attained concentrations of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Indeed, oxidative stress is known to cause damage to important cellular biomolecules [ 56 ]. Besides, accumulating evidence has shown that due to its sulfites and its derivatives, SMB can cause oxidative stress as a result of sulfite oxidation and DNA damage in vital organs such as the liver, brain, lung, and spleen [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, oxidative stress is known to cause damage to important cellular biomolecules [ 56 ]. Besides, accumulating evidence has shown that due to its sulfites and its derivatives, SMB can cause oxidative stress as a result of sulfite oxidation and DNA damage in vital organs such as the liver, brain, lung, and spleen [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, soldiers frequently report acute trauma pain and are often hemodynamically unstable shortly after a severe combat injury. Opioids can further increase hemodynamic instability in some patients (Gordon et al, 2004), a serious medical concern.…”
Section: Use Of Vr Distraction For Active Component Soldiersmentioning
confidence: 99%